Faktor Risiko Stunting pada Balita di Indonesia - Bayu Prabowo; Yuly Peristiowati (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the risk factors for stunting in toddlers in Indonesia. The method used is a literature review. The research results show that, in general, three factors influence the risk of checking in Indonesian toddlers, including Parental factors consisting of maternal factors, elements during pregnancy and genetic factors, toddler factors, and environmental factors. The most dominant factors influencing the incidence of stunting in toddlers in this literature review are low maternal education level, low birth weight, inadequate exclusive breastfeeding for children, and consumption of foods that are not varied and have a variety of proteins. In conclusion, three factors can influence stunting in toddlers in Indonesia: parental factors, toddler factors, and environmental factors. Keywords: Risk Factors, Growth Disorders, Indonesia, Stunting